2008
DOI: 10.1196/annals.1428.070
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of MexicanBabesia bovisIsolates UsingmsaandssrRNAGene Sequences

Abstract: Variable merozoite surface antigens of Babesia bovis are exposed glycoproteins having a role in erythrocyte invasion. Members of this gene family include msa-1 and msa-2 (msa-2c, msa-2a(1), msa-2a(2), and msa-2b). Small subunit ribosomal (ssr)RNA gene is subject to evolutive pressure and has been used in phylogenetic studies. To determine the phylogenetic relationship among B. bovis Mexican isolates using different genetic markers, PCR amplicons, corresponding to msa-1, msa-2c, msa-2b, and ssrRNA genes, were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 16 publications
3
11
0
2
Order By: Relevance
“…Further, with the exception of the isolates designated Veracruz 2/Guerrero (EF640951/EF640947) and Tamaulipas 2 (EF640949), whose sequences are more divergent and belong to the cluster group 2, all genotypes previously identified in Mexico belong to cluster group 1 identified in this study. A recent study by Genis et al using MSA2a and 2b (other members of the VMSA family) also demonstrated that B. bovis isolates in Mexico group into “clades” with no geographical association of genotypes [9]. The high sequence identity, with only a few amino acid substitutions between members of the cluster groups in our study and those reported previously throughout Mexico could be accounted for in several ways.…”
Section: Discussionsupporting
confidence: 78%
“…Further, with the exception of the isolates designated Veracruz 2/Guerrero (EF640951/EF640947) and Tamaulipas 2 (EF640949), whose sequences are more divergent and belong to the cluster group 2, all genotypes previously identified in Mexico belong to cluster group 1 identified in this study. A recent study by Genis et al using MSA2a and 2b (other members of the VMSA family) also demonstrated that B. bovis isolates in Mexico group into “clades” with no geographical association of genotypes [9]. The high sequence identity, with only a few amino acid substitutions between members of the cluster groups in our study and those reported previously throughout Mexico could be accounted for in several ways.…”
Section: Discussionsupporting
confidence: 78%
“…The involvement of genetic diversity in the immune evasion of B. bovis is well documented in the literature (Berens et al, 2005;Leroith et al, 2005). Consequently, the genetic diversity among the MSA genes has been studied in several endemic countries (Altangeral et al, 2012;Berens et al, 2005;Borgonio et al, 2008;Genis et al, 2008Genis et al, , 2009Leroith et al, 2005;Molad et al, 2014;Nagano et al, 2013;Sivakumar et al, 2013b;Tattiyapong et al, 2014). Almost all these studies invariably focused on the genetic diversity of the MSA genes of B. bovis derived from cattle, whereas B. bovis in buffaloes has rarely been investigated, although this host species is considered to play a significant role in its epidemiology (da Silva et al, 2013;Elsify et al, 2015;He et al, 2012;Sivakumar et al, 2013a).…”
Section: Discussionmentioning
confidence: 98%
“…Studies conducted in Australia (Berens et al, 2005;Leroith et al, 2005), Sri Lanka (Sivakumar et al, 2013b), the Philippines (Tattiyapong et al, 2014), Thailand (Simking et al, 2013), Israel (Molad et al, 2014), Brazil (Nagano et al, 2013), and Mexico Genis et al, 2008Genis et al, , 2009) have found that B. bovis isolates in these countries are genetically diverse, according to their MSA gene sequences.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Her iki antijen de farklı Babesia suşları arasında yüksek immunojenik T ve B hücre epitoplarına sahip olup aşı çalışmalarında kullanıl-maktadır. B. bovis yüzey antijenlerinden msa-2c geni, diğer yüzey antijenlerine göre farklı suşlar arasında yüksek korunmuşluk özelliği ile ön plana çıkmaktadır (3,10,14,33). B. bigemina rap-1 proteinleri de benzer şekilde farklı coğrafyalardaki suşlar arasında yüksek düzeyde konservatif özellik gösteren antijenlerdir (25,32).…”
Section: Introductionunclassified